PENGARUH STRUKTUR MODAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Abdul Hadi Sirat; Muhsin N Bailusy (Jurnal Manajemen Sinergi, 2019)
This study aims to determine the effect of capital structure andinstitutional ownership on firm value with dividend policy as an intervening variable. In manufacturing companies listed on the IndonesiaStock Exchange with a sample of 39 companies. The analytical methodused is path analysis. The observation period for 5 years and theresearch data are secondary data obtained from www.idx.co.id.The results showed that the direct effect of capital structure variables(DER) had a negative and significant effect on firm value, institutionalownership variables (INST) had a negative and significant effect on firmvalue, dividend policy (DPR) had a positive but not significant effect onfirm value. While the indirect effect of capital structure (DER) on firmvalue (INST) through dividend policy (DPR) is that dividend policy cannotmediate the effect of capital structure on firm value and indirect influenceof institutional ownership (INST) on firm value (INST) through dividendpolicy (DPR) is that dividend policy cannot mediate the effect ofinstitutional ownership (INST) on firm value (INST)